Association between TNF Receptors and KIM-1 with Kidney Outcomes in Early-Stage Diabetic Kidney Disease. Issue 2 (February 2022) - Waijer, Simke W.; Sen, Taha; Arnott, Clare; Neal, Bruce; Kosterink, Jos G.W.; Mahaffey, Kenneth W.; Parikh, Chirag R.; de Zeeuw, Dick; Perkovic, Vlado; Neuen, Brendon L.; Coca, Steven G.; Hansen, Michael K.; et al.
Visual Abstract: Abstract : Background and objectives: Clinical trials in nephrology are enriched for patients with micro- or macroalbuminuria to enroll patients at risk of kidney failure. However, patients with normoalbuminuria can also progress to kidney failure. TNF receptor-1, TNF receptor-2, and kidney injury marker-1 (KIM-1) are known to be associated with kidney disease progression in patients with micro- or macroalbuminuria. We assessed the value of TNF receptor-1, TNF receptor-2, and KIM-1 as prognostic biomarkers for CKD progression in patients with type 2 diabetes and normoalbuminuria. Design, setting, participants, & measurements: TNF receptor-1, TNF receptor-2, and KIM-1 were measured using immunoassays in plasma samples from patients with type 2 diabetes at high cardiovascular risk participating in the Canagliflozin Cardiovascular Assessment Study trial. We used multivariable adjusted Cox proportional hazards analyses to estimate hazard ratios per doubling of each biomarker for the kidney outcome, stratified the population by the fourth quartile of each biomarker distribution, and assessed the number of events and event rates. Results: In patients with normoalbuminuria ( n =2553), 51 kidney outcomes were recorded during a median follow-up of 6.1 (interquartile range, 5.8–6.4) years (event rate, 3.5; 95% confidence interval, 2.6 to 4.6 per 1000 patient-years). Each doubling of baseline TNF receptor-1 (hazard ratio, 4.2; 95% confidence interval, 1.8 to 9.6) and TNF receptor-2 (hazard ratio, 2.3; 95% confidence interval, 1.5 to 3.6) was associated with a higher risk for the kidney outcome. Baseline KIM-1, urinary albumin-creatinine ratio, and eGFR were not associated with kidney outcomes. The event rates in the highest quartile of TNF receptor-1 (≥2992 ng/ml) and TNF receptor-2 (≥11, 394 ng/ml) were 5.6 and 7.0 events per 1000 patient-years, respectively, compared with 2.8 and 2.3, respectively, in the lower three quartiles. Conclusions: TNF receptor-1 and TNF receptor-2 are associated with kidney outcomes in patients with type 2 diabetes and normoalbuminuria. Clinical Trial registry name and registration number: CANagliflozin cardioVascular Assessment Study (CANVAS), NCT01032629